Pengaruh Kompensasi, Worklife Balance dan Keterlibatan Kerja Terhadap Intention to Stay pada Karyawan Sentral Cargo Cabangsolo Raya - Latifah Hikmatul Nuzul Azizah; Nike Larasati (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The purpose of this study is to analyse the effect of compensation, work-life balance, and work engagement on the intention to stay among employees of Sentral Cargo Solo Raya Branch. This study uses quantitative data. The data source used is primary data. The population in this study consists of 45 employees of Sentral Cargo Solo Raya Branch, so the sampling technique used in this study is saturated sampling. The data analysis techniques used in this study were descriptive analysis, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results of this study indicate that compensation does not have a significant effect on the intention to stay among employees of Sentral Cargo Solo Raya Branch, thus the first hypothesis is not proven to be true. Work-life balance has a positive and significant effect on the intention to stay among employees of Sentral Cargo Solo Raya Branch, thus proving the second hypothesis to be true. Work engagement has a positive and significant effect on the intention to stay among employees of Sentral Cargo Solo Raya Branch, thus proving the third hypothesis to be true. The F test results show a significance value of 0.000, which means that the model is accurate in predicting the influence of compensation, work-life balance, and work engagement on the intention to stay at Sentral Cargo Solo Raya Branch. The R2 test result of 0.813 means that the contribution of the influence of the variables of compensation, work-life balance and work engagement on the intention to stay is 0.813, while the remaining (100% - 81.3%) = 18.7% is explained by other variables outside the model, such as leadership, job satisfaction, work stress and so on.